Age-Related Macular Degeneration and Mortality: A Systematic Review and Meta-Analysis. (4th May 2017) - McGuinness, Myra B.; Karahalios, Amalia; Finger, Robert P.; Guymer, Robyn H.; Simpson, Julie A.
ABSTRACT: Purpose : Age-related macular degeneration (AMD) is the leading cause of severe, irreversible vision loss in older adults. Evidence for an association between AMD and mortality remains inconclusive despite evidence for an association with cardiovascular and inflammatory diseases. We aim to compare all-cause, cardiovascular and cancer mortality between those with early or late AMD and control study participants. Methods : A protocol was registered at PROSPERO (CRD42015020622). A systematic search of Medline (Ovid), PubMed, and Embase (Ovid) was conducted on 6 June 2015. Reference lists from identified studies and four clinical trial registries were searched for additional studies. Participants were required to be over the age of 40 years, and AMD status must have been objectively assessed. The Risk Of Bias In Non-Randomized Studies – of Interventions (ROBINS-I) tool was used to assess the risk of bias. Random-effects meta-analyses were performed. Results : A total of 12 reports from 10 studies were included in the meta-analysis. Late AMD was associated with elevated rates of all-cause (nine studies, hazard ratio (HR) 1.20, 95% confidence interval, CI, 1.02–1.41) and cardiovascular mortality (six studies, HR 1.46, 95% CI 1.13–1.98), but early AMD was not (all-cause mortality, 10 studies, HR 1.06, 95% CI 0.98–1.14; cardiovascular mortality, five studies, HR 1.12, 95% CI 0.96–1.31). There was no evidence of an association between early or late AMD and cancer mortality (early AMD, three studies, HR 1.17, 95% CI 0.78–1.75; late AMD, three studies, HR 1.01, 95% CI 0.77–1.33). Conclusion : Late AMD is associated with increased rates of all-cause and cardiovascular mortality, suggesting shared pathways between late AMD and systemic disease.